2016
DOI: 10.1590/1516-4446-2015-1789
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and clinical correlates of rapid cycling bipolar disorder: a cross-sectional study

Abstract: Objective: Rapid cycling (RC) is a feature of bipolar disorder (BD) that has been associated with worse outcome and more severe disability. Our goal was to investigate the association of demographic and clinical factors with RC. Methods: We compared RC and non-rapid cycling (NRC) BD patients from the Brazilian Research Network in Bipolar Disorder (BRN-BD) regarding age at onset of BD; total number of episodes; previous number of manic, depressive, mixed, and hypomanic episodes; polarity of the first episode; g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(62 reference statements)
3
13
0
Order By: Relevance
“…The association between RC and a longer duration of illness has been reported in other socio-cultural contexts [22, 41], supporting the hypothesis of some authors that consider RC a transient phenomenon [17–19, 42] which could be more frequent in the advanced stages of illness. In this sense, RC could be considered a clinical marker of chronicity [18] rather than a variable of poor prognosis of subjects with recent onset of illness.…”
Section: Discussionsupporting
confidence: 83%
“…The association between RC and a longer duration of illness has been reported in other socio-cultural contexts [22, 41], supporting the hypothesis of some authors that consider RC a transient phenomenon [17–19, 42] which could be more frequent in the advanced stages of illness. In this sense, RC could be considered a clinical marker of chronicity [18] rather than a variable of poor prognosis of subjects with recent onset of illness.…”
Section: Discussionsupporting
confidence: 83%
“…This chronic immune dysfunction, including activation of cell-mediated immunity, development of autoimmune disorders and systemic inflammation, may be a primary consequence of inflammatory processes and/or result from altered central nervous system integrity, and thus be a reflection of neuroprogression (8,9). Furthermore, it is expected that such chronic low-grade inflammation contributes to the development of comorbidities in BD, such as obesity, metabolic syndrome, cardiovascular disorders and autoimmune disorders as well as a more severe clinical presentation (5,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…By definition, individuals with rapid cycling BD experience higher NoE than nonrapid cyclers; around seven times as many manic and twice to three times as many depressive episodes, adding to the overall burden. Rapid cycling is also linked with poorer outcomes, and it is difficult to disentangle impacts associated with accumulating NoE alone from those related to episodic frequency . Furthermore, rapid cycling is typically a transitory phenomenon, adding to attribution difficulties.…”
Section: The Construct Of Noe: Conceptual Issuesmentioning
confidence: 99%
“…Rapid cycling is also linked with poorer outcomes, and it is difficult to disentangle impacts associated with accumulating NoE alone from those related to episodic frequency . Furthermore, rapid cycling is typically a transitory phenomenon, adding to attribution difficulties. Despite this complexity, research exploring the impact of NoE has demonstrated that these effects cannot be wholly accounted for by rapid cycling; for example differences in Lithium responsiveness based on NoE were independent of rapid cycling status .…”
Section: The Construct Of Noe: Conceptual Issuesmentioning
confidence: 99%